Endothelial-to-mesenchymal transition contributes to endothelial dysfunction and dermal fibrosis in systemic sclerosis. Issue 5 (6th January 2017) - Manetti, Mirko; Romano, Eloisa; Rosa, Irene; Guiducci, Serena; Bellando-Randone, Silvia; De Paulis, Amato; Ibba-Manneschi, Lidia; Matucci-Cerinic, Marco
Abstract : Objective: Systemic sclerosis (SSc) features multiorgan fibrosis orchestrated predominantly by activated myofibroblasts. Endothelial-to-mesenchymal transition (EndoMT) is a transdifferentiation by which endothelial cells (ECs) lose their specific morphology/markers and acquire myofibroblast-like features. Here, we determined the possible contribution of EndoMT to the pathogenesis of dermal fibrosis in SSc and two mouse models. Methods: Skin sections were immunostained for endothelial CD31 or vascular endothelial (VE)-cadherin in combination with α-smooth muscle actin (α-SMA) myofibroblast marker. Dermal microvascular ECs (dMVECs) were prepared from SSc and healthy skin (SSc-dMVECs and H-dMVECs). H-dMVECs were treated with transforming growth factor-β1 (TGFβ1) or SSc and healthy sera. Endothelial/mesenchymal markers were assessed by real-time PCR, immunoblotting and immunofluorescence. Cell contractile phenotype was assayed by collagen gel contraction. Results: Cells in intermediate stages of EndoMT were identified in dermal vessels of either patients with SSc or bleomycin-induced and urokinase-type plasminogen activator receptor (uPAR)-deficient mouse models. At variance with H-dMVECs, SSc-dMVECs exhibited a spindle-shaped appearance, co-expression of lower levels of CD31 and VE-cadherin with myofibroblast markers (α-SMA+ stress fibres, S100A4 and type I collagen), constitutive nuclear localisation of the EndoMT driver Snail1 and an ability to effectively contract collagen gels. Treatment of H-dMVECs either with SSc sera or TGFβ1 resulted in the acquisition of a myofibroblast-like morphology and contractile phenotype and downregulation of endothelial markers in parallel with the induction of mesenchymal markers. Matrix metalloproteinase-12-dependent uPAR cleavage was implicated in the induction of EndoMT by SSc sera. Conclusions: In SSc, EndoMT may be a crucial event linking endothelial dysfunction and development of dermal fibrosis.